(untitled) (World Bulletin of Physical Education and Sports Science, 2026)
This article presents an analysis of the study of model characteristics of weight and height indicators of highly qualified female freestyle wrestlers in the process of selecting young female freestyle wrestlers and their correct orientation towards sports specialization. The main goal of the research is to analyze the anthropometric indicators of female freestyle wrestlers who have achieved high sports results, as well as to scientifically substantiate the process of selection and orientation of young athletes based on these indicators. During the study, specific model indicators characteristic of height, body weight, and weight categories of highly qualified female freestyle wrestlers were determined, and their interrelationships were analyzed. Also, based on the results obtained, practical recommendations were developed that serve the correct selection of young female wrestlers at the initial stage of training, the determination of a weight category corresponding to their morphological characteristics, and the improvement of sports results. The research results will contribute to the improvement of the process of selection, qualification, and orientation of young female freestyle wrestlers towards sports specialization.